Small Molecule Palmatine Targeting Musashi-2 in Colorectal Cancer - Zhang, Xue; Su, Kaiyan; Liu, Yifan; Zhu, Darong; Pan, Yuting; Ke, Xisong; Qu, Yi (Frontiers in Pharmacology, 2022)
Musashi-2 (MSI2) is an evolutionally conserved RNA binding protein, and recently considered as an attractive therapeutic target in a wide spectrum of malignancies. However, MSI2 engaged mRNAs are not well profiled, and no MSI2-dependent antagonist is available so far. In the study, we created MSI2 knockout cancer cells, and demonstrated that MSI2 is required for the survival of colorectal cancer HCT116 cells but not non-small cell lung cancer (NSCLC) A549 cells. In addition, global profiling of the transcriptome and proteomic of MSI2 knockout colorectal cells revealed 38 candidate MSI2 targeted genes. In a loss-rescue screening, Palmatine was identified as a functional MSI2 antagonist inhibiting MSI2-dependent growth of colorectal cancer cells. Finally, we confirmed that Palmatine directly bound to MSI2 at its C-Terminal. Our findings not only indicated MSI2 as a promising therapeutic target of colorectal cancer, but also provided a small molecule Palmatine as a direct and functional MSI2 antagonist for cancer therapy.